Assessment of quantification accuracy and image quality of a full‐body dual‐layer spectral CT system. (20th December 2017) - Ehn, Sebastian; Sellerer, Thorsten; Muenzel, Daniela; Fingerle, Alexander A.; Kopp, Felix; Duda, Manuela; Mei, Kai; Renger, Bernhard; Herzen, Julia; Dangelmaier, Julia; Schwaiger, Benedikt J.; Sauter, Andreas; et al.
Abstract: The performance of a recently introduced spectral computed tomography system based on a dual‐layer detector has been investigated. A semi‐anthropomorphic abdomen phantom for CT performance evaluation was imaged on the dual‐layer spectral CT at different radiation exposure levels (CTDIvol of 10 mGy, 20 mGy and 30 mGy). The phantom was equipped with specific low‐contrast and tissue‐equivalent inserts including water‐, adipose‐, muscle‐, liver‐, bone‐like materials and a variation in iodine concentrations. Additionally, the phantom size was varied using different extension rings to simulate different patient sizes. Contrast‐to‐noise (CNR) ratio over the range of available virtual mono‐energetic images (VMI) and the quantitative accuracy of VMI Hounsfield Units (HU), effective‐Z maps and iodine concentrations have been evaluated. Central and peripheral locations in the field‐of‐view have been examined. For all evaluated imaging tasks the results are within the calculated theoretical range of the tissue‐equivalent inserts. Especially at low energies, the CNR in VMIs could be boosted by up to 330% with respect to conventional images using iDose/spectral reconstructions at level 0. The mean bias found in effective‐Z maps and iodine concentrations averaged over all exposure levels and phantom sizes was 1.9% (eff. Z) and 3.4% (iodine). Only small variations were observed with increasing phantom size (+3%) while the bias was nearly independent of the exposure level (±0.2%). Therefore, dual‐layer detector based CT offers high quantitative accuracy of spectral images over the complete field‐of‐view without any compromise in radiation dose or diagnostic image quality.